Listening to Collaborate: Professional Development for Postsecondary Agricultural Education and Training Instructors Teaching Technical Subjects in Nigeria - Matt Spindler; Benjamin Ogwo (Journal of International Agricultural and Extension Education, 2014)
Implementing high quality professional development for postsecondary Agricultural Education and Training (AET)instructors is a critical step in facilitating inclusive economic development in Nigeria. Most technical agricultural graduate programs in Nigeria do not include training in instructional methods, creating lesson plans, or assessment techniques and lecturers are usually forced into learning the craft of teaching through trial and error. Unfortunately, poor teaching and a lack of innovative strategies do little to break the status quo view that agriculture is a distasteful option for youths. It is likely that economic and social progress in Nigeria will be attenuated if AET systems cannot attract and motivate capable students to engage in addressing the critical problems surrounding food security, sustainability, and climate change. The purpose of this grounded theory study was to create a conceptual model for addressing the process oriented professional development needs of postsecondary AET instructors teaching technical subjects in Nigeria
Keywords: Agricultural Education; Nigeria; Professional Development; Process Approach